Student retention through customized service processes - Jung, Reinhard; Kochbeck, Jessica; Nagel, Annett (Towards Sustainable Society on Ubiquitous Networks, Proceedings of the 8th IFIP Conference on e-Business, e-Services, and e-Society (I3E 2008), 2008)
Due to the Bologna declaration and the subsequent switch to the bachelor/master system, student mobility is rising and competition among universities across Europe becomes intense. Furthermore, students are demanding comfortable information and communication solutions. Hence, universities are required to align educational- and service-processes more closely to their students. This paper presents an innovative approach to adapt modern concepts of Customer Relationship Management (CRM) to institutions of higher education in order to retain students at their university. Furthermore, an architecture is presented which is capable of integrating university legacy systems with state of the art CRM technology.